Respiratory Muscle Dysfunction in Congestive Heart Failure: Clinical Correlation and Prognostic Significance - Meyer, F. Joachim; Borst, Mathias M.; Zugck, Christian; Kirschke, Andreas; Schellberg, Dieter; Kübler, Wolfgang; Haass, Markus (Circulation (New York, N.Y.), 2001)
Background —In congestive heart failure (CHF), the prognostic significance of impaired respiratory muscle strength has not been established. Methods and Results —Maximal inspiratory pressure (Pi max ) was prospectively determined in 244 consecutive patients (207 men) with CHF (ischemic, n=75; idiopathic dilated cardiomyopathy, n=169; age, 54±11 years; left ventricular ejection fraction [LVEF], 22±10%). Pi max was lower in the 244 patients with CHF than in 25 control subjects (7.6±3.3 versus 10.5±3.7 kPa; P =0.001). The 57 patients (23%) who died during follow-up (23±16 months; range, 1 to 48 months) had an even more reduced Pi max (6.3±3.2 versus 8.1±3.2 kPa in survivors; P =0.001). Kaplan-Meier survival curves differentiated between patients subdivided according to quartiles for Pi max ( P =0.014). Pi max was a strong risk predictor in both univariate ( P =0.001) and multivariate Cox proportional hazard analyses ( P =0.03); multivariate analyses also included NYHA functional class, LVEF, peak oxygen consumption (peak V̇ o 2 ), and norepinephrine plasma concentration. The areas under the receiver-operating characteristic curves for prediction of 1-year survival were comparable for Pi max and peak V̇ o 2 (area under the curve [AUC], 0.68 versus 0.73; P =0.28), and they improved with the triple combination of Pi max , peak V̇ o 2 , and LVEF (AUC, 0.82; P =0.004 compared with AUC of Pi max ). Conclusions —In patients with CHF, inspiratory muscle strength is reduced and emerges as a novel, independent predictor of prognosis. Because testing for Pi max is simple in clinical practice, it might serve as an additional factor to improve risk stratification and patient selection for cardiac transplantation.